Pengaruh Bahan Baku terhadap Karakteristik Produk Hasil Pirolisis: Studi Literatur - Sheila Novella Arvenia; Mohamad Rangga Sururi; Novi Fitria (Jurnal Serambi Engineering, 2025)
The global climate change phenomenon is prompting initiatives aimed at transitioning energy sources towards more sustainable pathways. Pyrolysis technology offers significant potential in the conversion of biomass and plastic waste into alternative energy sources. The objective of this literature review is to analyze the effect of feedstock type on pyrolysis product characteristics and its potential as an energy source. The results of the literature study indicated that the feedstock from biomass possessed a lower calorific value in comparison to waste composed of polymer compounds. The pyrolysis process yields three primary byproducts: char, bio-oil, and gas. Char can be utilized as a solid fuel, such as briquettes. The processing of bio-oil into liquid fuel, bioethanol, is a viable option. The pyrolysis gas is a versatile material that can be utilized as a fuel for stoves and generators. Pyrolysis, a promising technology, has the potential to convert biomass and plastic waste into alternative energy. The type of feedstock employed is a critical factor in determining the quality and quantity of pyrolysis products. Through process optimization and technological development, pyrolysis has the potential to play a substantial role in reducing reliance on fossil fuels and addressing environmental concerns.